Association between surgeon special interest and mortality after emergency laparotomy. Issue 7 (25th April 2019) - Boyd-Carson, H; Doleman, B; Herrod, P J J; Anderson, I D; Williams, J P; Lund, J N; Tierney, G M; Murray, D; Hare, S; Lockwood, S; Oliver, C M; Spurling, L J; et al.
Abstract: Background: Approximately 30 000 emergency laparotomies are performed each year in England and Wales. Patients with pathology of the gastrointestinal tract requiring emergency laparotomy are managed by general surgeons with an elective special interest focused on either the upper or lower gastrointestinal tract. This study investigated the impact of special interest on mortality after emergency laparotomy. Methods: Adult patients having emergency laparotomy with either colorectal or gastroduodenal pathology were identified from the National Emergency Laparotomy Audit database and grouped according to operative procedure. Outcomes included all-cause 30-day mortality, length of hospital stay and return to theatre. Logistic and Poisson regression were used to analyse the association between consultant special interest and the three outcomes. Results: A total of 33 819 patients (28 546 colorectal, 5273 upper gastrointestinal (UGI)) were included. Patients who had colorectal procedures performed by a consultant without a special interest in colorectal surgery had an increased adjusted 30-day mortality risk (odds ratio (OR) 1·23, 95 per cent c.i. 1·13 to 1·33). Return to theatre also increased in this group (OR 1·13, 1·05 to 1·20). UGI procedures performed by non-UGI special interest surgeons carried an increased adjusted risk of 30-day mortality (OR 1·24, 1·02 to 1·53). The risk of return to theatre was not increased (OR 0·89, 0·70 to 1·12). Conclusion: Emergency laparotomy performed by a surgeon whose special interest is not in the area of the pathology carries an increased risk of death at 30 days. This finding potentially has significant implications for emergency service configuration, training and workforce provision, and should stimulate discussion among all stakeholders. Graphical Abstract: Mortality after emergency laparotomy is increased at 30 days if the operation is not performed by a consultant with a special interest in the area of pathology (colorectal or gastroduodenal). Specialist interest affects outcome